Investigation on the Properties of Gneiss under Different Ground Stresses - Rui Wang; Yuncai Wang; Xianghui Deng; Yuan Qin; Bingxin Xie (Sensors, 2022)
Initial geostress has great influence on the properties of gneiss. The physical and mechanical properties of gneiss vary considerably due to different initial geostresses, which exert a huge effect on the stability of underground engineering. In order to explore the influence of initial ground stress on the properties of gneiss. Changes in the physical properties (e.g., P-wave velocity and volumetric weight), mechanical properties (e.g., compressive strength, elastic modulus, and residual strength) and failure mode of gneiss are analyzed by conducting physical and mechanical tests on gneiss in different ground stress areas. The results show that high geostress can improve the pre-peak mechanical properties of gneiss, and weaken its post-peak mechanical properties. When the initial geostress is greater, the pre-peak mechanical properties are better, and the post-peak mechanical properties are worse. The failure mode of gneiss under high ground stress is primarily brittle failure. When the initial ground stress is greater, brittleness is stronger. According to the research results of this paper, it can provide the basis for the optimization and improvement of underground engineering support in gneiss strata with high geostress. The research results have important reference value and guiding significance for underground engineering construction in high geostress gneiss areas.